Prognostic significance of quantitative bacteremia in septicemic melioidosis. - Walsh, A; Smith, MD; Wuthiekanun, V; Suputtamongkol, Y; Chaowagul, W; Dance, D; Angus, B; White, N (1995)
Pour-plate blood cultures were performed for 418 adult patients with suspected septicemic melioidosis in order to determine the relationship between quantitative bacterial counts in blood and mortality. Of 108 patients whose hemocultures yielded Burkholderia pseudomallei, 53% had < 10 cfu/mL and 24% had > 100 cfu/mL. High blood bacterial counts were more common than reported previously with regard to other gram-negative septicemias and were significantly associated with the development of hypotension (P = .008) and a fatal outcome (P = .0001). The overall mortality was 63% (95% CI, 53%-72%); however, counts of < or = 1 cfu/mL were associated with a mortality of 42% (95% CI, 28%-58%), compared with 96% (95% CI, 80%-100%) with counts of > 100 cfu/mL. Heavy bacteremia (> 50 cfu/mL) is common in septicemic melioidosis and is usually fatal.